Review: Potensi Spesies Croton Sebagai Anti-HIV - Hanifah, Nidaa; Dila Ayu Apsari, Ratna; Anis Jungjunan, Repita; Muhammad Wahid Fadhilah, Reyhan; Virginia Kiik, Rosa; Oktapiani, Selvia; Maria Ina Ose Tapowolo, Selviana; Musdalifah, Siti; Pudjiastuty, Tiara; Septiani, Yuni (LP4M STIKes Karsa Husada Garut, 2025)
Introduction: HIV is a retrovirus that attacks the immune system and can develop into AIDS if not treated. Drug resistance and therapy limitations are major challenges. The genus Croton (Euphorbiaceae) has potential as a source of anti-HIV compounds, with species such as C. megalocarpus, C. dichogamus, and C. oligandrus capable of inhibiting reverse transcriptase and reactivating latent viruses. Methods: This narrative review, analyzes the literature from 2020–2024. Results: Studies show that bioactive compounds from Croton, particularly diterpenoids and flavonoids, have anti-HIV activity through the inhibition of reverse transcriptase and reactivation of latent viruses. Conclusion: The genus Croton has the potential to be a new source of anti-HIV drugs. With the increasing drug resistance, the development of bioactive compounds from Croton could become a promising therapeutic alternative.Keywords: Croton, anti-VIV, natural compound